Nickel Diplomacy: The Geopolitics of Indonesia’s Downstream Policy and the Global Electric Vehicle Supply Chain - Kusuma, Darmawan Putra; Dewi, Komang Purnama; Atmika, Gede Surya (Indonesia Discourse, 2025)
As the world pivots toward renewable energy, Indonesia has positioned itself as a pivotal player in the global Electric Vehicle (EV) supply chain by leveraging its status as the world’s largest nickel producer. This paper analyzes Indonesia’s "downstream" (hilirisasi) policy, which bans raw ore exports to compel domestic processing and battery manufacturing. Drawing on a political ecology framework and geopolitical discourse analysis, the study evaluates the trade-offs between national economic sovereignty and environmental sustainability. While the policy has successfully attracted massive investments from China and the West, it has simultaneously triggered international trade disputes (WTO) and raised concerns regarding the ecological footprint of high-pressure acid leaching (HPAL) technology. The research finds that "Nickel Diplomacy" serves as a double-edged sword: it empowers Indonesia in the global North-South negotiation but risks creating "green sacrifice zones" in mining regions like North Maluku. The paper concludes that for Indonesia’s transition to be truly "just," the discourse must move beyond GDP growth to include rigorous environmental accountability and indigenous land rights within the global green energy narrative.